Research and innovation - Rowarth, Jacqueline; Parsons, Anthony; Rasmussen, Susanne (New Zealand Science Review, 2014)
This article was prompted by the keynote address entitled ‘Highlights and lowlights of a science career in AgResearch’ given by Professor Susanne Rasmussen at the New Zealand Association for Women in the Sciences Conference, 2014.